Materi Interpretasi Kepemanduan Bahasa Inggris di Kampung Tajur Purwakarta - Zia Kemala; Adrian Agoes (STIEPAR YAPARI Bandung, 2021)
Kampung Tajur is a unique village located in the village of Pasanggrahan, Purwakarta. Kampung Tajur has a variety of ecotourism potentials, but Kampung Tajur needs to improve the quality of service, especially in terms of guiding services. Therefore, this study was conducted to determine the interpretation of the material for guidance in Kampung Tajur. The method used in this research is descriptive qualitative method. Data collection techniques used in this research are observation, interviews and literature study. This research has several key informants in Kampung Tajur, such as tour guides and informants from the tourism industry, pokdarwis and community leaders in Kampung Tajur. Based on the research results, it was found that at this time the guides in Kampung Tajur did not have any reference material for interpretation. Interpretation is only done as it is. Meanwhile, the development of interpretation material faces several obstacles, one of which is the lack of human resources as a tour guide, especially as a guide for foreign tourists, so it is necessary to make a bilingual guidebook containing interpretation material for guides. Therefore, it is necessary to produce a bilingual guidebook containing translated material for tour guides. This is necessary to anticipate differences in interpretation between guides and clarity of interpretation for tourists.